Studies on Novel Zwitterionic Hybrid Membranes: Adsorption Kinetic Models for Cobalt(II) Removal - Sun, Bo; Liu, Junsheng; Li, Meng (Asian Journal of Chemistry, 2015)
A zwitterionic hybrid membrane was prepared via the ring-opening of 1,3-propanesultone with the amine groups in the chains of 3-aminopropyl trimethoxysilane and a subsequent sol-gel process. Its adsorption performances for cobalt(II) removal were examined. On the basis of adsorption capacity of cobalt(II) ions on contact time, two-parameter kinetic equations were determined to evaluate the adaptivity of the fitted model. It was found that the adsorption of cobalt(II) ions on the prepared hybrid membrane fitted well with the Lagergren pseudo-second order model. The measurement of intraparticle diffusion confirmed that the adsorption of cobalt(II) ions on the hybrid membrane didn't only governed by intraparticle diffusion. Elovich model evidences that chemisorption didn't occur during the period of cobalt(II) removal. These findings are very useful in the removal of cobalt(II) ions from the stimulated radioactive wastewater and can be potentially used to dispose the radionuclide from the spent radioactive wastewater.